Typical Examples of Atoment Language Using - I. S. Anureev (Моделирование и анализ информационных систем, 2011)
Atoment is a domain-specific language of executable specifications, used to describe methods and techniques of program verification. In this paper a collection of typical examples of the use of the Atoment language, covering topics such as program models, operational, transformational and axiomatic semantics, formal specification of programming languages is presented.